VILLAGE UNIT COOPERATIVE BUSINESS INCOME ANALYSIS BASED ON MATHEMATICS MODEL (Case Study of Lau Gumba Village, Karo Regency) - Mika Debora Br Barus; Meigia Nidya Sari; Farah Soufika Thahirah (Proceeding International Seminar of Islamic Studies, 2022)
Mathematical modeling is the process of inferring a mathematical model of a phenomenon based on the assumptions used. The purpose of a mathematical model is to make decisions based on real situations by analyzing the model. This study aims to obtain a mathematical model of the income of Tomuan Holbung KUD in Asahan Regency, to determine the most dominant variable affecting income and to determine the perception of the Tomuan Holbung village community on income, the progress of KUD in the area. The method used in this study is a quantitative method. Data collection techniques through literature study. Data analysis used linear regression analysis so that a mathematical model was obtained, namely Y = 228961 935 - 0.197x e. The constant is 228961935 which means if income (Y) does not exist or is zero (zero), then the SHU (Y) in the cooperative will decrease by Rp. 289,61,935. While the value of b (regression coefficient) shows a negative value of 0.197. The value of 0.197 means that if the income is zero then the SHU remains the same and each additional 1 sale reduces the SHU by 0.197.Keywords:Mathematical modeling, business income, KUD.